2003
DOI: 10.1590/s0100-29452003000100021
|View full text |Cite
|
Sign up to set email alerts
|

Severidade da antracnose e perda de matéria fresca de frutos de dez procedências de maracujázeiro-doce (Passiflora alata Dryander) em dois ambientes de armazenamento

Abstract: Frutos de maracujá-doce de dez procedências foram avaliados quanto à severidade da antracnose (Colletotrichum gloeosporioides Penz.) e quanto à perda de matéria fresca em dois ambientes de armazenamento: câmara fria (5ºC e UR de 90%) e em ambiente de sala (23±1ºC e UR de 65±5%). Plantas provenientes de frutos colhidos em estado nativo ou adquiridos nos mercados da Central de Abastecimento de São Paulo- CEAGESP, procedências A, B e C; Viçosa-MG, procedência D; Tomé-Açu-PA, procedência E; Itacoatiara-AM, procedê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
4
0
2
Order By: Relevance
“…The storage conditions and the use of packaging and wax provided significant changes in the physiological variables, which directly influenced the post-harvest shelf life of P. alata fruits. The same occurred in the reports of Junqueira et al (2003) and Silva et al (1999).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The storage conditions and the use of packaging and wax provided significant changes in the physiological variables, which directly influenced the post-harvest shelf life of P. alata fruits. The same occurred in the reports of Junqueira et al (2003) and Silva et al (1999).…”
Section: Resultssupporting
confidence: 81%
“…This variation did not have deleterious action on the fruits, it showed that both packages were permeable to these gases, which allowed gas exchanges with the environment, avoiding the occurrence of physiological imbalances that could have a negative effect on the quality of the fruits during the 14 days of storage (Oliveira et al, 2014;Rinaldi et al, 2017b). As for the phytosanitary evaluation, fruits kept at 10 °C did not show symptoms of infestation by any post-harvest pathogens during the 14 days of storage (Benato et al, 2002;Junqueira et al, 2003;Muniz et al, 2003;Arruda et al, 2011a). The result confirms the reports of Junqueira et al (2003), Arruda et al (2011a), Rotili et al (2013a), Rotili et al (2013b) and Rinaldi et al (2017b) who also reported a significant reduction in the incidence of post-harvest pathogens in sweet, yellow, and setacea passion fruit stored under refrigeration, regardless of whether they were wrapped in plastic films or not.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A utilização de refrigeração na conservação de frutos do maracujazeiro já é recomendada para as espécies P. setacea, P. alata e P. edulis, pois proporciona um maior tempo de prateleira, além de preservar vários parâmetros fisiológicos importantes, como, por exemplo, a textura da casca, além de reduzir a infestação por agentes fúngicos (Rinaldi et al, 2019a;Rinaldi et al, 2017c;Rotili et al, 2013a;Junqueira et al, 2003). No entanto, não existem informações sobre o efeito desse tipo de armazenamento em P. cincinnata.…”
Section: Discussionunclassified